1995
DOI: 10.1128/mcb.15.10.5732
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase Expression in Transgenic Mouse Skin Causes Hyperkeratosis and Acanthosis and Increases Susceptibility to Tumorigenesis

Abstract: In a series of transgenic mice, the human tissue collagenase gene was expressed in the suprabasal layer of the skin epidermis. Visually, the mice had dry and scaly skin which upon histological analysis revealed acanthosis, hyperkeratosis, and epidermal hyperplasia. At the ultrastructural level, intercellular granular materials were absent in the transgenic skin epidermis but contact was maintained through the intact desmosomes. Despite a diversity of underlying etiologies, similar morphological hyperproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 30 publications
0
92
1
1
Order By: Relevance
“…Previous studies with intravital video microscopy showed the importance of MMP for creating and maintaining an environment that supports the tumor formation and growth (Koop et al, 1994;Chambers and Matrisian, 1997). Collagenase-1 expression in the skin of transgenic mice led to earlier onset and increased numbers of papillomas arising after chemical initiation and promotion (D'Armiento et al, 1995). We overexpressed MMP-1 gene in the dominant-negative STAT3-expressing cells by retrovirus transduction, but were unable to rescue the tumor growth in nude mice (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies with intravital video microscopy showed the importance of MMP for creating and maintaining an environment that supports the tumor formation and growth (Koop et al, 1994;Chambers and Matrisian, 1997). Collagenase-1 expression in the skin of transgenic mice led to earlier onset and increased numbers of papillomas arising after chemical initiation and promotion (D'Armiento et al, 1995). We overexpressed MMP-1 gene in the dominant-negative STAT3-expressing cells by retrovirus transduction, but were unable to rescue the tumor growth in nude mice (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Several chemical carcinogenesis models have been used to study MMPs in the early events of tumorigenesis. MMP-1 transgenics show increased susceptibility to skin carcinogens (D'Armiento et al, 1995), while MMP-9 null mice show decreased tumour incidence in another skin carcinogenesis model (Coussens et al, 2000). In the latter case, despite the deceased tumour incidence, tumours that do form are high-grade and more aggressive.…”
Section: Cell Divisionmentioning
confidence: 99%
“…For example, mice that express a human collagenase-1 (MMP-1) transgene in squamous epithelium develop hyperproliferative skin lesions, and although they fail to form tumors spontaneously, they are more sensitive to chemical carcinogens than their non-transgenic littermates (D'Armiento et al, 1995). Conversely, mice that lack stromelysin-3 (MMP-11) form fewer and smaller DMBA-induced tumors than wild-type mice (Masson et al, 1998).…”
Section: Other Mmps Can Promote Carcinogenesismentioning
confidence: 99%